Clinical significance of ovarian stromal blood flow in assessment of ovarian response in stimulated cycle for in vitro fertilization - Arora, Aashima; Gainder, Shalini; Dhaliwal, Lakhbir; Suri, Vanita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Several ultrasound parameters have been examined to predict the ovarian response to gonadotropins. The only parameter that has been conclusively proven to predict ovarian response is the antral follicle count. It has been suggested that ovarian blood flow may play a crucial role in the development of ovarian follicles. The present study was planned to prospectively analyse the effect of ovarian stromal blood flow on ovarian responsiveness in terms of number of oocytes retrieved in stimulated cycle for IVF. Methods: Fifty subjects between 22 to 37 years of age with male factor, tubal factor or unexplained infertility underwent controlled ovarian stimulation by the standard “Long protocol”. Ovarian stromal blood flow was recorded on baseline transvaginal sonography on day 2 or 3 of cycle and was correlated with number of oocytes retrieved in IVF cycle. Results: The ovarian stromal blood flow was found to be negatively correlated with age. The number of follicles formed in a subject after stimulation with gonadotropins was negatively correlated with ovarian stromal resistance index and pulsatility index. Conclusions: Ovarian blood flow predicts ovarian responsiveness and hence provides a non-invasive and cost effective prognostic factor of IVF outcome.